Green Cloud Computing: Perspective of Variety Coverage in Pre-Control - Badrulhisham Ismail, Mohd; Mohd Yusof, Yusnani; Hashim, Habibah (International Journal of Engineering and Technology, 2019)
In green computing, efficiency is required in consolidating virtual machines without degrading quality of service. This paper presents a study on dynamic VM Resource Allocation to produce lower power consumption and at the same time to optimize the stability. To achieve this objective, a new algorithm is used to calculate on the fly the Lower and Upper Threshold Limit using Statistical concept, and pre-control method is applied in order to optimize the stability of the process. The Pre-Control method sets the pre-control limits on upper and lower specification limits where process capability is based on meeting the conditions of a pre-control chart. The chart determines the type of variation the process is experiencing. Six sigma theories are then applied in order to get the desired range for the threshold limit. The results prove that dynamic VM Resource Allocation with a wider range of Green Region produce a more stable process.Â Â